THE EFFECT OF SLOW DEEP BREATHING ON REDUCING BLOOD PRESSURE IN ADULTS WITH HYPERTENSION - Musta’in; Indri Wulandari , Septiyana; Yuniarti, Tri; Irawan, Ady (LPPM Universitas Duta Bangsa Surakarta, 2023)
Hypertension is a condition where a person experiences blood pressure that exceeds normal blood pressure. Normal blood pressure in adults is 120/80 mmHg. The aim of this study was to determine the effect of the Slow Deep Breathing (SDB) technique on reducing blood pressure in adults with hypertension. The method used in this study was a pre-experimental study design with a total of 30 subjects selected by purposive sampling technique. Blood pressure data was taken before and after SDB intervention for 15 minutes. The results showed that there was a significant effect between SDB and a decrease in blood pressure in the elderly with hypertension (p <0.05). It is hoped that the SDB technique can be used as an alternative non-pharmacological therapy for elderly people with hypertension.